2016
DOI: 10.4172/2157-7471.1000380
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Analysis and Antibacterial and Cytotoxic Properties of Barleria lupulina Lindl. Extracts

Abstract: (India) during the month of June 2014, and identified by the experts of the department (specimen identification No Bot. and micro/199). The plant leaves were washed with running tap water to remove the adhered dust, dirt and unwanted particles from their surfaces. The leaves were shade dried at room temperature for 15 days and separately homogenized in domestic blender to get fine powders. The powders were stored in airtight container at room temperature for further studies. Bacterial cultures Five standard hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Presence of more or less similar phytoconstituents in varying amount in different solvents has also been reported by the other workers [ 6 , 16 , 20 , 21 ]. These results are similar to that of ethanolic extract recently reported by Kumari and Dubey [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Presence of more or less similar phytoconstituents in varying amount in different solvents has also been reported by the other workers [ 6 , 16 , 20 , 21 ]. These results are similar to that of ethanolic extract recently reported by Kumari and Dubey [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finally results in increase of concentration of lytic enzymes for more effective killing, which is ultimately reduced the paw odema after 48 and 72 h of treatment to the albino rats. Mazumder et al [ 12 ] also discussed a similar result on the effect of MEBL (300 mg/kg body weight) on spleen weight, WBC count, spleen leukocyte count and percentage increase in paw volume on delayed type hypersensitivity consisting footpad thickness. Methanolic extract of B. lupulina (600 mg/kg body weight) showed the positive effect ( P < 0.01) on all parameters than the dose of 300 mg/kg body weight.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Traditionally, B. lupulina was used to treat several diseases, including treating snake bites, dog bites, swelling, bleeding wounds, rheumatism, herpes simplex, and herpes zoster [ 10 , 11 ]. Studies have documented that B. lupulina has medicinal values, including anti-inflammation [ 12 ], antiviral [ 13 , 14 ], antibacterial [ 11 , 15 , 16 ], antidiabetic [ 17 ], cytotoxic [ 18 , 19 ], antidiuretic, and antiarthritic activity [ 20 , 21 ]. Several studies have also shown that the species possesses highly potential antioxidants and bioactive compounds used in treatments of various diseases and health issues [ 10 , 15 , 19 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some constituents of B. lupulina have been tested for antitumour activity in different carcinogenic models. B. lupulina has also been reported to possess a potent Antimicrobial [4,5,6], Anti-inflammatory [2, 7], Analgesic, Antiulcerogenic [7], Antidiabetic [8], Neuropharmacological [9], Toothache [10], Antibacterial [11], Anticancer [12], Antiartheritis, Acute and sub-chronic diuretic [13], Anti-viral [14]. However, very little is known regarding the molecular mechanisms by which they may exert their [12] and trypan blue exclusion dye method as per Jayashree and Thenmozhi [16].…”
Section: Introductionmentioning
confidence: 99%